Perancangan Aplikasi Pengamanan Pesan Teks Menggunakan Algoritma Kombinasi TTVC Dan OTP Berbasis Android Studio - Ratih Ningtyas; Andi Marwan Elhanafi; Mufida Khairani (SNASTIKOM, 2022)
Operating systems for mobile devices are growing. Android is a mobile operating system that is now very popular and widely used by people. For the purposes of the security aspect, Android has also provided specifically for cryptographic functions, such as encryption, decryption, and so on. Insecure message delivery can occur because when sending, the message sent is in the form of an original message so that if a message is taken from the delivery line, the message will be known by unauthorized parties. So we need a security on a message data. Encryption and decryption can be used to make messages so that they cannot be read or understood by other people who do not have access rights. The technique of securing data and information is known as cryptography. The use of the Triple Transposition Vigenere Cipher (TTVC) algorithm has been carried out on SMS security (Short Message Service) in order to maintain the integrity and security of the message content and cover gaps in SMS security. The message sent will be encrypted using the Triple Transposition Vigenere Cipher first so that the contents of the message can be read by the sender and recipient. Based on what has been discussed above the author will design a Text Message Security Application Using a Combination Algorithm of Triple Transposition Vigenere Cipher and One Time Pad Based on Android Studio to provide security for messages from unauthorized parties.